2018
DOI: 10.1111/ajt.14755
|View full text |Cite
|
Sign up to set email alerts
|

Burden and consequences of retained cardiovascular implantable electronic device lead fragments after heart transplantation

Abstract: We performed a retrospective review of 402 consecutive patients who underwent heart transplantation at our institution between January 2009 and March 2017. A retained cardiovascular implantable electronic device (CIED) fragment was identified after transplantation in 49 of the 301 patients (16.2%) with CIED at baseline. Patients with retained fragments had leads with longer dwell times (median 2596 [1982, 3389] vs 1384 [610, 2202] days, P < .001), higher prevalence of previously abandoned leads (14.3% vs 2.8%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In this study, 24% of the MRIs were thoracic. Similar data have been shown for MRIs of patients with CIED lead fragments . Our study adds to the accumulating safety data in patients with abandoned leads and represents the largest description thus far, including endocardial and epicardial PPM, ICD, subcutaneous high-voltage coils, and lead fragments.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, 24% of the MRIs were thoracic. Similar data have been shown for MRIs of patients with CIED lead fragments . Our study adds to the accumulating safety data in patients with abandoned leads and represents the largest description thus far, including endocardial and epicardial PPM, ICD, subcutaneous high-voltage coils, and lead fragments.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, as heart failure therapies advance, prosthetic valves and implantable devices might become more common in cases of infective endocarditis amongst SOT recipients. For example, Alvarez et al [18] recently reported that up to 16% of heart transplant recipients might have retained cardiac devices.…”
Section: Risk Factorsmentioning
confidence: 99%